Critical Factors Affecting the Efficiency of Information Security Risk Management in Business Organization: An Empirical Study - Oluwasefunmi, Arogundade; Folashade, Mogaji; Oluwafolake, Ojo; Yetunde, Alonge Christianah; Igbe, Tobore (Covenant Journal of Informatics and Communication Technology, 2021)
One vital issue in the management of organization is the security of information. Managing information security is a methodical approach of addressing organizational security threats and risks. Considering the increasing cost of implementing and maintaining information security, organizations need to differentiate between the controls needed and those which are crucial that should also be in line with the organization goals and objectives. In this paper, we proposed to analyse critical factors affecting the efficiency of information security management using Artificial Neuro-Fuzzy Inference System (ANFIS) approach and also evaluate the performance of the scheme. We adopted the use of questionnaires to collect responses (dataset) for the study. The questionnaire was designed and categorized based on15selected major critical factors affecting the efficiency of information security management. There were 51 respondents from users of information technology product, professional workers, students and teachers. The results from the model were obtained after training with iteration of 8 epochs, the best training result for R is 0.7743 and the average testing result is 0.7767. Also, a similar result (values) was obtained as the one from the descriptive analysis and this indicate that the performance of ANFIS model can predict the level of risk severity. The results showed that cost has the highest risk level depending on the outcomes from the respondent and the ANFIS model.